Fire Resistance in American Heavy Timber Construction History and Preservation - Heitz, Jesse (Springer International Publishing : Imprint: Springer, 2016)
This volume presents a history of heavy timber construction (HTC) in the United States, chronicling nearly two centuries of building history, from inception to a detailed evaluation of one of the best surviving examples of the type, with an emphasis on fire resistance. The book does not limit itself in scope to serving only as a common history. Rather, it provides critical analysis of HTC in terms of construction methods, design, technical specifications, and historical performance under fire conditions. As such, this book provides readers with a truly comprehensive understanding and exploration of heavy timber construction in the United States and its performance under fire conditions.